Analisis Penerapan Model Pembelajaran Contextual Teaching And Learning (CTL) pada Mata Pelajaran Otomatisasi Tata Kelola Humas dan Keprotokolan Kelas XI OTKP di SMK Negeri 2 Tuban - Genta Danu Prasetya; Novi Trisnawati (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
This study aims to find an overview of the process of Contextual Teaching and Learning (CTL) learning models on the subject of automation in public relations and protocol XI OTKP protocol management at SMK Negeri 2 Tuban. This research uses the literature study research method. The results showed that in the learning process subject matter of automation of public relations and protocol management has used a learning model that prioritizes group learning activities to understand the material. Efforts to instill values are given through a cooperative approach, while the type is adjusted to the subject matter approach analyzed by educators and focuses on the use of the cooperative learning model itself with the dominance of the type of Contextual Teaching and Learning (CTL) learning model. The learning process of students is by experiencing and not memorizing by constructing the knowledge of the students themselves. Thus creating a class learning process in which student become active participants rather than passive observers, and are responsible for learning.